SIV monoclonal antibody administration spanning treatment interruption in macaques delays viral rebound and selects escape variants - Hannah A. D. King; Daniel Brammer; Eric Lewitus; Christine M. Fennessey; Kimberly M. Manalang; Hannah R. Shrader; Shayne Andrew; Phillip Kuri; Matthew Lind; Phuc Pham; Eric Sanders-Buell; Hongjun Bai; et al. (Proceedings of the National Academy of Sciences, 2025)
HIV-1 envelope broadly neutralizing antibodies represent a promising component of HIV-1 cure strategies. To evaluate the therapeutic efficacy of combination monoclonal antibodies (mAbs) in a rigorous nonhuman primate model, we tested different combinations of simian immunodeficiency virus (SIV) neutralizing mAbs in SIVmac251-infected rhesus macaques. Antiretroviral therapy-suppressed animals received anti-SIV mAbs targeting multiple Env epitopes spanning analytical treatment interruption (ATI) in 3 groups (n = 7 each): i) no mAb; ii) 4-mAb combination; and iii) 2-mAb combination. Each mAb was administered at 15 mg/kg, and both mAb-treated groups received ITS103.01, a highly potent CD4-binding site targeting antibody. mAb treatment delayed viral rebound, lowered rebound viremia setpoint and viral diversity, and extended animal lifespan. Compared to controls, for which viremia rebounded 2 wk following ATI, mAb infusion delayed rebound for both groups ( P = 0.0003). Animals that received the 4-mAb regimen rebounded 3 to 6 wk post-ATI while the 2-mAb regimen rebounded 5 to 22 wk post-ATI. Envelope escape mutations emerged in rebound virus of mAb-treated animals that abrogated neutralization by ITS103.01, the most potent in the cocktail. These data demonstrate in vivo antiviral activity of SIV mAbs in the context of ATI via immune pressure dominated by the most potent mAb and highlight their potential in adjunctive therapeutic studies.